Functional Testing of Vestibulo-Spinal Contributions to Balance Control: Insights From Tracking Improvement Following Acute Bilateral Peripheral Vestibular Loss - Allum, John H. J.; Rust, Heiko Mario; Honegger, Flurin (Frontiers in Neurology, 2019)
Background: A battery of stance and gait tasks can be used to quantify functional deficits and track improvement in balance control following peripheral vestibular loss. An improvement could be due to at least 3 processes: partial peripheral recovery of sensory responses eliciting canal or otolith driven vestibular reflexes; central compensation of vestibular reflex gains, including substitution of intact otolith responses for pathological canal responses; or sensory substitution of visual and proprioceptive inputs for vestibular contributions to balance control. Results: We describe the presumed action of all 3 processes observed for a case of sudden incapacitating acute bilateral peripheral loss due to vestibular neuritis, for which otolith responses were largely unaffected, but caused pathological decreases in all canal-driven vestibular ocular reflex (VOR) gains. After 3 months of vestibular rehabilitation, balance control was normal but VOR gains remained low. Conclusions: This case illustrates the difficulty in predicting balance control improvements from tests of the 10 vestibular end organs and emphasizes the need to test balance control function directly in order to determine if balance control has improved and is normal again despite remaining vestibular sensory deficits.